Classification of The NTEV Problems on The Commercial Building - Mohd Abdul Talib Mat Yusoh; Saidatul Habsah Asman; Zuhaila Mat Yasin; Ahmad Farid Abidin (Institute of Advanced Engineering and Science, 2018)
Neutral to Earth Voltage (NTEV) is one of power quality (PQ) problems in the commercial building that need to be resolved. The classification of the NTEV problems is a method to identify the source types of disturbance in alleviating the problems. This paper presents the classification of NTEV source in the commercial building which is known as the harmonic, loose termination, and lightning. The Euclidean, City block, and Chebyshev variables for K-Nearest Neighbor (K-NN) classifying are being utilized in order to identify the best performance for classifying the NTEV problems. Then, S-Transform (ST) is applied as a pre-processing signal to extract the desired features of NTEV problem for classifier input. Furthermore, the performance of K-NN variables is validated by using the confusion matrix and linear regression. The classification results show that all the K-NN variables capable to identify the NTEV problems. While the K-NN results show that the Euclidean and City block variables are well performed rather than the Chebyshev variable. However, the Chebyshev variable is still reliable as the confusion matrix shows minor misclassification. Then, the linear regression outperformed the percentage close to a perfect value which is hundred percent.